La curación de contenidos educativos para desarrollar la competencia informacional de los estudiantes de tercer año de bachillerato de la unidad educativa nuestro mundo Eco- Rio, año lectivo 2020 - Castelo Flores, Enma (2023)
ABSTRACT: The objective of this study was to analyze the family socioeconomic level and its relationship with the state of oral health in adolescents from the EU Dr. Nicanor Larrea; it was observational and cross-sectional. The study population consisted of 147 adolescents from said EU and their respective representatives. The technique used was observation and, as an instrument, the medical records, additionally the socioeconomic level test. The results in terms of the socioeconomic level determined that 3 (2%) valued low socioeconomic status, 38 (25.9%) medium-low level, 59 (39.5%) typical medium level, 39 (26.5%) level medium-high and 9 (6.1%) assessed a high level. The researcher used the CPOD index to establish the relationship between the family socioeconomic level and the oral health of adolescents, which decreased as the socioeconomic status improved. The Kruskal Wallis test estimated a significance p<0.05, which allowed us to conclude that the CPOD index if it is related to socioeconomic level, finding significant differences in the mean value of CPOD in the different socioeconomic strata while through the IHOS analysis, the mean values of plaque, calculus, and gingivitis decrease with improvement in socioeconomic level, but these variations are not significant. Therefore, the family's socioeconomic status influences adolescents' oral health; for this reason, it is necessary for more oral health prevention strategies for students and parents. Keywords: Socioeconomic level, oral health, adolescents, promotion, prevention